PRAKTEK PEMBUATAN PRASARANA ANGKUTAN DI AREAL HUTAN RAWA SUMATRA SELATAN (The practice of in'(rastructure. construction in swamp forest areas of -South Sumatra) - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1990)
A atucly of the practice of in(rastiucture (railroads)construction in wamp forest areasof South Sumatra was carried out  in 1989. The intention is to find  various aspects of  field operations in that specific area and their poaible  con- aequencea.It  ill found that aupports of rails in swamp forest areas are consisted of either 4 or 5 layers of logs. In constructing those railroads, logs used vary from 140 to 177 cu.m/km  with an averageof 166 cu.m/km.   Including the value of this material into calculationgives the total construction cost of railroadto the amount of around Rp 16.5 million per km.Soil diatyrbance iB found to be minimal due to narrow railroadclearingand /'lat topography. Problema identified in the field are the uceaive   use of logs for railroad construction and large amount of othe- logs scattered and abandon- ed around railroadsand manual skidding (kuda-kuda) roads.  It  seems that there is a strong need for the government and conceaionaires to seriously pay  attention and create better instructions and actions in managingthose valuable swamp (orats  on a sustainable basis.